Non-profit organizations' participation in the management of public programmes: The case of the Czech Republic - Oto Potluka; Martin Spacek; Jiri Remr (University of Basel, Center for Philanthropy Studies (CEPS), 2015)
EU Cohesion Policy requires the interaction of public, private and non-profit sectors in policy making. The case of the Czech Republic enables us to identify the major obstacles to the successful implementation of this approach as the Czech population perceives the ability of NGOs to influence policies at the lowest level among all the EU member states. The goal of the study is to identify and explain the determinants of success and failure regarding NGOs' participation in designing public programmes. The methodology includes a combination of in-depth interviews with NGOs' representatives and public servants, a review of official documents, a focus group, and a stakeholders' review of the study's conclusions. The main obstacles to the implementation of the partnership principle are the following: insufficient capacities among NGOs; fluctuations in participating public servants and NGO representatives; dependence of partnership on personal contacts; late start and non-consultative, informative character of partnership.
Keywords: L31; R50; R58; 330; Cohesion Policy; Non-profit organizations; Participation; Partnership Principle; The Czech Republic